The Portrayal of the COVID-19 Pandemic in the Media - Bryła, Władysława; Bryła-Cruz, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of the paper is to present and discuss the portrayal of the COVID-19 pandemic in the media. Our primary focus is on Polish press articles, supplemented by occasional references to international sources. The analysis reveals that, much like in previous pandemics, the media narrative around COVID-19 is heavily metaphorical, aiming to simplify the understanding of this unfamiliar event. The most common metaphors involve war and battle, which have sparked controversy and significant criticism for their militaristic connotations. Our paper also examines alternative representations of the pandemic, such as natural disasters (with the fire metaphor being particularly apt), sports (including football, mountain climbing, and marathons), and other innovative comparisons (comparing the pandemic to an animal, driving a car, etc.).